RHoMIS – a rural household multiple indicator survey tool - CGIAR Research Program on Livestock (2018)
RHoMIS has now been applied in 27 countries by different research partners (ICRAF, CSIRO, Bioversity, WUR), NGOs (Tree Aid) and donors (IFAD, EU, USAID Innovation Labs). Over 20,000 households have been surveyed. Please see www.rhomis.org.